Optimasi Pemasaran Digital untuk Meningkatkan Visibilitas UMKM BB Glow Mask Batam - Quinn, Fionna; Candy, Candy (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
BB Glow Mask Batam is an MSME that focuses on retailing local skincare products under the brand TeenEx, which has obtained official approval from BPOM. In its marketing actions, the MSME owner relies solely on WhatsApp and word-of-mouth recommendations to establish relationships with customers as its primary strategy. Based on interview results, it was revealed that the owner of BB Glow Mask Batam faced challenges when attempting to use other marketing channels such as Instagram and Shopee. Despite recognizing the significant potential for skincare products on Shopee, the UMKM owner found it difficult to operate the platform due to the complexity of information required to register a store and products on Shopee. Consequently, an initiative was taken to assist BB Glow Mask Batam in enhancing its business exposure through the development of more optimal marketing strategies. Additionally, the UMKM owner received education on digital marketing. The outcomes of this initiative include the design of Instagram content, a business logo, Linktree, and the registration of a Shopee account. The implementation of marketing strategies on Instagram yielded positive responses, as evidenced by positive data from Instagram Insights after the content was shared. Furthermore, statistics from Linktree indicated an increase in clicks and visits from a significant audience. By effectively leveraging these platforms, the business has the opportunity to reach a broader market and enhance its visibility.